Preference-Performance Dissociation in Golf Putting - Ziv, Gal; Lidor, Ronnie; Elbaz, Liav; Lavie, Matar (Frontiers in Psychology, 2020)
The purpose of the current study was to examine the effectiveness of providing autonomy to learners and the phenomenon of preference-performance dissociation on a closed, self-paced motor task – putting in golf, when using different placements of a visual aid (a large circle) around a golf hole. Seventy-six participants were assigned to four experimental groups: (a) a visual aid placed behind the hole (V-behind group), (b) a visual aid placed in front of the hole (V-in-front group), (c) a visual aid placed around the hole (V-around group), and (d) a visual aid placed according to the participant’s preference (V-pref group). Participants performed five pre-trials, 50 training putts from a distance of 2 m, a retention task (12 putts) from a distance of 2 m, and a transfer task (12 putts) from a distance of 2.5 m. The retention putts and transfer putts were performed 48 h after the training putts. The participants’ subjective assessment of the helpfulness of the circle was also measured. It was found that in the retention task, putting consistency was lower in the V-in-front group compared to the V-around and V-pref groups. However, the subjective assessment of the helpfulness of the circle was higher in the V-in-front group. In addition, the low consistency of the V-in-front group was alleviated in the participants in the V-pref group who chose to place the circle in front of the hole. In contrast, the subjective assessment of the helpfulness of the circle was low in the V-in-front group. These findings suggest that while providing autonomy – that is, when the participant is able to choose for him/herself – can improve motor learning, there may be a dissociation between an individual’s subjective assessment and the actual helpfulness of a visual aid. This dissociation may be termed preference-performance dissociation, and coaches and instructors who teach closed, self-paced motor skills should be aware of the fact that when providing learners with the autonomy to choose a practice aid in order to improve their skills, some may not choose the aid that is effective for them.